1963
DOI: 10.2307/1126737
|View full text |Cite
|
Sign up to set email alerts
|

Task Complexity and IQ as Variables in Piaget's Problem of Conservation

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1966
1966
1981
1981

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…These results provide confirmation for the findings of such British and North American research workers as Carpenter (1955), Beard (1960aBeard ( , 1960b, Elkind (1961), andFeigenbaum (1963) that concept development is more closely linked to the growth of general intellectual ability than just to CA (or general maturational level). It is interesting to observe that the reported correlations of concept development with MA have in general been higher than those with IQ, as one would expect if CA in fact played a lesser role than MA.…”
Section: Discussionsupporting
confidence: 81%
“…These results provide confirmation for the findings of such British and North American research workers as Carpenter (1955), Beard (1960aBeard ( , 1960b, Elkind (1961), andFeigenbaum (1963) that concept development is more closely linked to the growth of general intellectual ability than just to CA (or general maturational level). It is interesting to observe that the reported correlations of concept development with MA have in general been higher than those with IQ, as one would expect if CA in fact played a lesser role than MA.…”
Section: Discussionsupporting
confidence: 81%
“…Love11 and Ogilvie (1961), for example, found that children who were able to conserve weight in one test were non-conservers in another. Similar findings have been made at various age levels and in respect of different capacities by Dodwell (1962), Uzgiris (1964), Feigenbaum (1963) and Stone and Ausubel (1969) among many others. There is nothing in stage theory to predict these phenomena: they are known only post facto.…”
Section: Stages Of Development: Help or Hindrance Young Children?supporting
confidence: 84%
“…Even more striking than this lack of agreement about age norms, however, is the almost total absence of information available about the withinconcept developmental sequence. Our only source of information about initial and intermediate competence is the verbal explanation data provided by the Genevans and by a few early replication studies (e.g., Dodwell 1961Dodwell , 1962Feigenbaum 1963;Hood 1962). As discussed earlier, numerous welltaken criticisms have been made of these investigators' reliance on verbal justifications-unreliability, inflated likelihood of type II error, underestimation of young children's knowledge-but no proposals of substitute methods for obtaining this type of qualitative information have been forthcoming.…”
Section: Methodsmentioning
confidence: 99%
“…For the within-concept sequences, the controversy has focused more on methodological issues. Piaget and his followers have relied heavily on verbal explanation data to support their claim that children progress through qualitatively discrete knowledge states on their way to mastering concepts (e.g., Dodwell 1961Dodwell , 1962Feigenbaum 1963;Hood 1962;Lovell 1961;Pinard & Laurendeau 1969). This practice has been criticized for a variety of reasons: it has been said to entail overly great risk of type II error (Brainerd 1977), to be insensitive to early forms of reasoning competence (Braine 1959), to be inapplicable to very young children (Bryant 1974), and to be generally unreliable (Keating 1980;Neimark 1975).…”
Section: Introductionmentioning
confidence: 99%